PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KARYAWAN TERHADAP KEPUASAN KERJA PT NUGRA KARSERA - Imam Wibowo; Finna Destirahayu (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
Competition in the globalization era for human resources has become the center of attention for achieving success in the company. This intense competition is marked by the company by the increase in human resources who will be able to master technology quickly, adaptively and responsively in the face of changes in technology. This study aims to examine the influence of work environment and employee motivation on job satisfaction at PT Nugra Karsera. This study uses a quantitative approach. The population in this study is the total number of employees of PT Nugra Karsera as many as 65 people. The sampling technique in this study used the Isaac and Michael tables, so it can be seen that the number of samples is 55 respondents. The data collection technique in this study used a questionnaire that had been tested for its validity and reliability. The data analysis method used in this study is multiple linear regression analysis and simple with hypothesis testing, namely the F test and t test. The results of this study indicate that work environment variables and motivation have a positive and significant effect on job satisfaction.